Methods of estimation of motor development children with damage brain - Kempka-Dobra, Ewa; Steinborn, Barbara (Przewodnik Lekarza/Guide for GPs, 2005)
The aim of this study was to made methods of estimation of motor development children with damage of brain. Evaluation of children was conducted with utilization of elements ”Munich Functional of Development Diagnostics”. In connection to this method four spheres of motor development of children were separated and observed: crawling on all fours, sitting down, going and seizing. The influence of damaged brain on development of function was estimated in researched group.